Discovering Hidden Temporal Patterns in Behavior and Interaction T-Pattern Detection and Analysis with THEME™ - Magnusson, Magnus S.; Burgoon, Judee K.; Casarrubea, Maurizio (Neuromethods, 2016)
XVIII, 333 p. 100 illus., 55 illus. in color.